2012
DOI: 10.1074/jbc.m111.262543
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of the Neuronal Nicotinic Receptor α7 by HIV Glycoprotein 120

Abstract: Approximately 30 -50% of the >30 million HIV-infected subjects develop neurological complications ranging from mild symptoms to dementia. HIV does not infect neurons, and the molecular mechanisms behind HIV-associated neurocognitive decline are not understood. There are several hypotheses to explain the development of dementia in HIV ؉ individuals, including neuroinflammation mediated by infected microglia and neuronal toxicity by HIV proteins. A key protein associated with the neurological complications of HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 51 publications
4
47
0
Order By: Relevance
“…Inhibitors of CXCR4 and α7-nAChRs suppressed gp120-induced mucus formation in NHBE cells, but the CXCR4 inhibitor did not block nicotine-induced mucus production (not shown), suggesting that α7-nAChRs are downstream of CXCR4 in the gp120-induced mucus formation in NHBE cells. More recently, binding of gp120 to CXCR4 was shown to upregulate the expression nAChRs in neuronal cells [40]. Together these results suggest that CXCR4 communicates with nAChRs in regulating biological functions, including mucus production.…”
Section: Discussionmentioning
confidence: 80%
“…Inhibitors of CXCR4 and α7-nAChRs suppressed gp120-induced mucus formation in NHBE cells, but the CXCR4 inhibitor did not block nicotine-induced mucus production (not shown), suggesting that α7-nAChRs are downstream of CXCR4 in the gp120-induced mucus formation in NHBE cells. More recently, binding of gp120 to CXCR4 was shown to upregulate the expression nAChRs in neuronal cells [40]. Together these results suggest that CXCR4 communicates with nAChRs in regulating biological functions, including mucus production.…”
Section: Discussionmentioning
confidence: 80%
“…Recent studies have revealed that α7 nAChR is a critical link between inflammation and neurodegeneration, which is closely associated with Alzheimer’s disease, might be a potential therapeutic target for the pathogenicities-caused by HIV-1 and drugs of abuse38. It has been shown that gp120 could up-regulate α7 nAChR, which is a previously unrecognized contributor to the neurotoxicity associated with HAND38.…”
Section: Disscussionmentioning
confidence: 99%
“…Recent studies have revealed that α7 nAChR is a critical link between inflammation and neurodegeneration, which is closely associated with Alzheimer’s disease, might be a potential therapeutic target for the pathogenicities-caused by HIV-1 and drugs of abuse38. It has been shown that gp120 could up-regulate α7 nAChR, which is a previously unrecognized contributor to the neurotoxicity associated with HAND38. It has been shown that enhancing peptides (EPs) derived from the co-receptor binding region of gp120 could promptly accelerated the formation of amyloid fibrils through the EP-derived nanofibers and significantly enhance HIV-1 infection3940.…”
Section: Disscussionmentioning
confidence: 99%
“…The gp120 molecule, a surface protein of the HIV virus capsule, has been shown to bind to the highly calcium permeable homomeric α7-nAChR [80], upregulating receptor production, leading to astrocyte death, and subsequent apoptosis of nearby neurons, particularly in the striatum [81]. Another group also showed that gp120 may facilitate the production of reactive oxygen species that increase apoptotic loss of dopamine neurons in the substantia nigra, causing some of the Parkinsonian-like motor impairments that are present in HAND [82].…”
Section: Normal Cognitive Agingmentioning
confidence: 99%